ANALISIS FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN TERHADAP DANA HIBAH GLOBAL FUND PENDERITA TBC PADA DINAS KESEHATAN PROVINSI MALUKU - Darmayanti Abutalib (Soso-Q : Jurnal Manajemen, 2019)
The Global Fund is a non-governmental international organization engaged in the health sector, which aims to attract, channel and manage resource to fight against HIV / AIDS, Tuberculosis and Malaria. The management of the Global Find is under supervision of the Health Office of Maluku Province. The aims of this study was to determinate the effect of planning documents, administration records, human resources competency, and inventory money on the absorption of the Global Fund grant budget for TB Patiens in Health Office of Maluku Provincial both partially and simultaneously.This study was a descriptive quantitative research using survey menhod. The data were analyzed by using multiple linear regression analysis, conducting classical assumption tests first.The results showed that: Planning documents affected budget absorption. This showed the good or bad planning documents presented by Health Office of Maluku province would affect budget absorption; Adminitration records did not affect budget absorption. This showed that the good or bad administrative registration system at Health Office of Maluku Province did not budget absorption. Human resource competence did not affect budget absorption. This showed that the grant did not depend on human resources competency at health Office of Maluku Province. Planning documents had a positive effect on budgetabsorption. This showed that the more payment form would affice absorption Province. Inventory money did not affect the absorption budget. This showed that the better the inventory money mechanism for Global Fund grants for TB patien at the Health office of Maluku Province did not necessarily increase budget absorption. Simultaneously independent variables affectd the dependent variable.  Keywords : Global Fund Grants, Planning Documents, Administration recorts Human Resource Competency, Procurement Document Inventory Money on Budget Absorption.